Investigation of Water Absorption and Color Change of Indirect Composite Resins - Bilge Ersöz; Numan Aydın; Elif Aybala Oktay; Nur İskender; Serpil Karaoğlanoğlu (Ankara University, 2021)
Color Stability, Indirect composite resins, Water absorption